EQUIVALENT REPRESENTATIONS OF HIDDEN MARKOV MODELS - SETIAWATY, B. (MILANG Journal of Mathematics and Its Applications, 2003)
In this article, we classify the class of hidden Markov models through the laws of the observation processes, since the Markov chains are not observable. Here, we also present some properties regarding this classiﬁcation.